Towards Mathematical Literacy in the 21st Century: Perspectives from Singapore - Ng Kit Ee Dawn (Southeast Asian Mathematics Education Journal, 2011)
The Organization for Economic Cooperation and Development (OECD) postulates that a major focus in education is to promote the ability of young people to use their knowledge and skills to meet real-life challenges (OECD, 2006). PISA, an international standardised assessment of students’ (aged 15) performance in the literacies of mathematics, science, and reading, was developed by the OECD in 1997 to evaluate the achievement of students who are about to finish their key stages of education (Anderson, Chiu, & Yore, 2010). The concept of mathematical literacy has been defined and interpreted in various ways as recorded in the curriculum documents around the world. This paper will share perspectives from Singapore on how mathematical literacy is interpreted in the mathematics curriculum through the use of three tasks: interdisciplinary project work, applications, and modelling. It will surface challenges to improving the mathematical literacy of students when using such tasks.